GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENERAPKAN MANAJEMEN BERBASIS SEKOLAH DI MIN KETAHUN - Elirina Elirina Elirina (UNIVERSITAS BENGKULU, 2016)
The principal's leadership style is one of the crucial factors determining the performance of teachers and educational success in school. This study provides conclusionsindicate that: (1) Principal in implementation style participatory, democratic, healthy school climate and harmonious in schools. Such as upholding the values of togetherness and carry out thevision of school using participative style while describing school rules that have been set using partisivatif and democratic, (2) Principal to improve teacher discipline like timeliness comes toschool with a schedule that has been set using the style of a healthy school climate and harmonious, (3) Principal be fair in the distribution of tasks and well-being guided by regulationsand programs using participatory leadership style, democratic, healthy school climate and harmonious.Keywords: participatory, leadership, style